Factors Influencing Consumers In Buying Decisions For Decorative Flowers (Case Study Vivi Flower) In Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency - Irmayani, Irmayani; Saskia, Saskia; Nurhaedah, Nurhaedah (Jurnal Agricultural Science, 2024)
Bulucenrana Village is one of the villages in Pitu Riawa District, Sidenreng Rappang Regency, where most of the area is plantation areas, both long-term and medium-term crops. Vivi Flower is one of the decorative flower selling businesses in Bulucenrana Village. There are various kinds of decorative flowers that are sold at varying prices. There are several factors that influence consumers in purchasing decisions for decorative flowers, including psychological factors, price and location. The aims of this study were: 1) to find out what factors influence consumers in purchasing decorative flower decisions at Vivi Flower, Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency and 2) to find out what factors most dominantly influence consumers in purchasing decorative flower decisions at Vivi Flower Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency. This type of research is quantitative research. The research sample consisted of 38 respondents who were ornamental flower consumers who visited Vivi Flower. The instrument used in this study was a research questionnaire consisting of several questions regarding the variables studied. The data analysis technique used was descriptive statistical analysis and multiple regression analysis with the help of the SPSS 22 program. From the results of the study, it was obtained: 1) Factors that influence consumers in buying ornamental flowers at Vivi Flower, Bulucenrana Village, Pituriawa District, Sidenreng Rappang Regency are psychological factors and price factors and 2) The most dominant factor affecting consumers in purchasing decisions for decorative flowers at Vivi Flower, Bulucenrana Village, Pituriawa District, Sidenreng Rappang Regency is the price factor based on a coefficient of determination of 75.2%.